OUTDOOR ACTIVITIES MODIFICATION AND RECURRENT INTRAORAL HERPES IN ELDERLY PATIENT: CASE REPORT - Adi Ahmad Yusuf; Wahyu Hidayat (Dentino : Jurnal Kedokteran Gigi, 2022)
Background: Infections caused by the herpes simplex virus (HSV) are infections that often occur in the oral and perioral areas. One of the recurrent herpes infections in the orofacial area is recurrent intraoral herpes (RIH).  Purpose: To discuss treatment management of RIH and lifestyle modification in physically active elderly patients. Case Report: A 67 year old male patient came to Oral Medicine clinic of RSGM Unpad with complaint of recurrent ulcers in the oral cavity, this ulcers started 3 days earlier and no history of fever. Patient daily ativities including walking 8 to 9 km a day. Laboratory examinations showed an increase value of IgG HSV-1. Intraoral examination, multiple ulcers were found on the left lateral tongue, ventral tongue, upper labial mucosa, right labial mucosa and left buccal mucosa. Case Management: The patient was given acyclovir 200 mg, 5 times a day for 1 week. After one week, there was no improvement, new ulcers still appeared,we suggest that this is due to the patient still active as usual. Patient was given acyclovir 400 mg 5 times a day for 1 week, multivitamins and chlorhexidine digluconate 0,12% mouthwash, the patient was also instructed to reduce the frequency of outdoor activity and use sunscreen. On the third visit, patient was comfortable, the ulcers had healed and there were no new lesions. Conclusion: In addition to systemic medical treatment management for RIH, it is also necessary to consider lifestyle modifications in these patients by reducing the intensity of physical activity and use sunscreen.